CONTRIBUTION FOR ENERGY AND ENVIRONMENTAL MAINTENANCE IN HUAMBO CITY - César Pakissi (European Regional Science Association (ERSA), 2011)
Huambo city although currently not industrialized, list an increasing degradation of its environment in terms of atmospheric and noise pollution, for the fact of current lack of supply of electric energy, to stimulate the use of individual form, electric chain generators on the part of the city dwellers, fact that this stops beyond if disclosing as an authentic threat for the environment, besides impracticable under the economic point of view. This situation together whith an inapropriate use of the potentialities of power plants cleaner than the region offers becomes a worry subjects which are analyzed in the present work about the contribution for energy and environmental maintenance in Huambo city, on this basis the diagnosised problem and use of diverse methods, from the hypothesis that the individual production of energy in Huambo city is the main factor responsible for the atmospheric pollution that is seen in this region. Potential was analyzed three scenes that allows to characterize the current problems of energy supply in Huambo city, its economic and ambient impacts and is considered alternative that they point viable power plants under the economic and ambient point of view.
Keywords: 330